تفويض المرفق العام مفهومه، أسسه، أشكاله، في ظل المرسوم التنفيذي 18/199 (Revue El-Wahat pour les Recherches et les Etudes, 2020)
The Public Utility Shall Provide Services To Citizens Or Satisfy Their Needs For The Public Interest, And Since The Needs Evolve With The Development Of Society, Public Facilities Must Keep Pace With This Development, In Particular With Its Management Style, Especially After The Failure Of More Traditional Methods (Direct Exploitation, The Public Institution). That Is Due To The Development Of The Economy And The Growth Of Civil Awareness, In Addition To The State Relinquishing Control Over Economic Facilities, Which Required Alternatives To Operate Them Represented In The Mechanism Of Delegation Of The Public Facility, Which Took Its Place As A General Concept That Includes A Number Of Contracts (Concession, Rent, Incentive Agency, Management), Which Are Assigned To Public Or Private Entities In The Conduct Of Facility, And This Is Reflected In The Presidential Decree 15/247, The Executive Decree 18/199, Which Was Applied To Him. Keywords -Management, General Attachment, Authorization, Forms